PENGEMBANGAN E-RAPORT KURIKULUM 2013 BERBASIS WEB PADA SMA TUNAS MEKAR INDONESIA - Ajeng Savitri Puspaningrum; Neneng Neneng; Intan Saputri; Fenty Ariany (Universitas Lampung, 2020)
SMA Tunas Mekar Indonesia is one of Lampung Province schools that uses the 2013 curriculum. The assessment reporting process of student learning skills and achievement by teachers uses report cards that are distributed to parents at the end of each semester. In the managing the report card data process, there are several obstacles, namely the obstruction of grade recapitulation because the subject teacher is late in sending student grades, it takes a long time in managing grades because the processing value data done repeatedly from the attendance recap report then the application of Microsoft Excel and the report books are recapitulated by staff allows data writing errors. The solution developed for this problem is to build a Web-Based E-Report Card Application that will help SMA Tunas Mekar Indonesia by simplifying and accelerating teachers and homeroom teachers in assessing student learning outcomes reports process on inputting student scores. In this application, teachers and homeroom teachers no longer need to send assessment data via email, because the data entered is already integrated with other data. So that it doesn't take a long time to enter student grades, and minimize the damage and loss of report card data. The application built has provided complete information regarding student report card information and helps schools in reporting student grades based on the testing results using ISO 25010 standart with a percentage of success with a total average of 92.82%.